The study of the speed and statistical security of cryptographic hashing algorithms - Кузнецов, О.О.; Тимченко, В.А.; Лисицький, К.Є.; Родінко, М.Ю.; Луценко, М.С.; Шеханін, К.Ю.; Колгатін, А.О. (Radiotekhnika, 2019)
Comparative studies of cryptographic hashing algorithms are being carried out, which are used (or can be applied) in modern decentralized blockchain systems. In particular, hashing speed of action is studied on different desktop systems, the number of clock cycles of the computing system per byte (Cycles / byte), the volume of the hashed message per second (MB / s) and the number of generated hash codes per second (KHash / s) are estimated. Additionally, the speed of action speed of action of individual cryptographic hashing functions on graphical computers is investigated. To evaluate statistical security, we study the initial sequences of cryptographic hash functions when they process excessive input data (which are generated using a conventional counter). For comparative studies of statistical security indicators, the NIST STS (Statistical Test Suite for Random and Pseudorandom Number Generators for Cryptographic Applications) technique is used, which is recommended by the National Institute of Standards and Technology for the study of random and pseudorandom number generators for cryptographic applications.